Understanding the biosimilar approval and extrapolation process—A case study of an epoetin biosimilar. (August 2016) - Agarwal, Amit B.; McBride, Ali
Abstract: The World Health Organization defines a biosimilar as "a biotherapeutic product which is similar in terms of quality, safety and efficacy to an already licensed reference biotherapeutic product." Biosimilars are biologic medical products that are very distinct from small-molecule generics, as their active substance is a biological agent derived from a living organism. Approval processes are highly regulated, with guidance issued by the European Medicines Agency and US Food and Drug Administration. Approval requires a comparability exercise consisting of extensive analytical and preclinical in vitro and in vivo studies, and confirmatory clinical studies. Extrapolation of biosimilars from their original indication to another is a feasible but highly stringent process reliant on rigorous scientific justification. This review focuses on the processes involved in gaining biosimilar approval and extrapolation and details the comparability exercise undertaken in the European Union between originator erythropoietin-stimulating agent, Eprex ®, and biosimilar, Retacrit™.